2013
DOI: 10.1080/10253866.2013.763603
|View full text |Cite
|
Sign up to set email alerts
|

The impact of aesthetics on the Celtic craft market

Abstract: Fillis, IRThe impact of aesthetics on the Celtic craft market http://researchonline.ljmu.ac.uk/3826/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU Research Online to facilitate their private study or for non-commercial research. You may not en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…national myths, cultural contradictions, institutional logics, and new technologies) into aestheticized versions. Through the aestheticization of markets, particular myths are made tangible, graspable, and experientable-not only on the level of brands but as a market genre (Fillis 2014). This is particularly evident in Celtic craft markets, Ostalgie retro markets, and Nordic food markets (Fillis 2014;Gyimóthy 2017;Brunk, Giesler, and Hartmann 2018;Ulver 2019), which interweave object-focused experiences with cultural myths by tying specific cultural narratives to consumption experiences that are specific to market genres.…”
Section: Aestheticization As Market Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…national myths, cultural contradictions, institutional logics, and new technologies) into aestheticized versions. Through the aestheticization of markets, particular myths are made tangible, graspable, and experientable-not only on the level of brands but as a market genre (Fillis 2014). This is particularly evident in Celtic craft markets, Ostalgie retro markets, and Nordic food markets (Fillis 2014;Gyimóthy 2017;Brunk, Giesler, and Hartmann 2018;Ulver 2019), which interweave object-focused experiences with cultural myths by tying specific cultural narratives to consumption experiences that are specific to market genres.…”
Section: Aestheticization As Market Processesmentioning
confidence: 99%
“…For instance, aestheticization is a recurrent analytical subtext in prior work on taste formation in aestheticized markets, emphasizing mutual cooperation and a complex mixture of intellectual and sensory pleasures as well as the learned response involved in aesthetic experiences (Arsel and Bean 2013;Maciel and Wallendorf 2017;Maciel and Fischer 2020). Likewise, other studies imply that the processes of aestheticization reframe symbolic resources around subcultures and collective performances (Schouten and McAlexander 1995;Kates 2002;Kozinets 2002;Goulding and Saren 2009); branding practices (Holt 2002;Brown, Kozinets, and Sherry 2003;Wu, Borgerson, and Schroeder 2013); and markets enchanted by authenticity, craft, artisanship, and "the handmade" (Brown, Hirschman, and Maclaran 2000;Campbell 2005;Fillis 2014;Ulver 2019). Furthermore, aestheticization resonates in studies that analyze consumption contexts of retro consumption and marketing (Belk and Costa 1998;Brown, Kozinets, and Sherry 2003;Brown 2018;Brunk, Giesler, and Hartmann 2018) and spectacular environments (Maclaran and Brown 2005;Marrewijk and Broos 2012;Nuttavuthisit 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of studies, including the recent ones (e.g., Andersson et al, 2018;Crick et al, 2018;Fillis et al, 2017;Pitchayadol et al, 2018;Toghraee et al, 2017;Weerawardena et al, 2017;Yang & Gabrielsson 2017) in the review have adopted the case study methods to explore the phenomenon of EM. This indicates a high relevance of EM with the case study method, particularly due to the heterogeneous nature of SMEs (Fillis 2014). However, on the other hand, there are other useful methods as well, for example, ethnographic research (Martin 2009), and biographical research (Fillis 2015), that were not greatly tapped by the researchers so far.…”
Section: Future Researchmentioning
confidence: 99%
“…These contributions have a keen focus on understanding architectural elements of strategic communication (visual design and advertising rhetoric) as means to distinguish national brands and identities on a multicultural and transnational market. Regionalist studies have identified the domination of auto-exoticising cultural stereotypes, for example, when contrasting "Celtic" vs "Saxonian" entrepreneurial ethos (remarked by creativity and intuition) on the Irish craft market (Fillis, 2014), promoting linguistic idiosyncrasies (Strandberg, 2020) or a unique "taste iconicity" for Indian cuisine (Varman, 2017). So, what does another regional perspective add to the field of place branding?…”
mentioning
confidence: 99%